Dental caries: Impact of tobacco product among tobacco chewers and tobacco smokers - Vidya G. Doddawad; S. Shivananda; Navia Jose Paul; J. Chandrakala (Elsevier, 2022)
Objective: Tobacco is the most significant social burden and the leading cause of death. Tobacco is derived from "Nicotiana tabacum" which has nicotine as the main component. There are various disadvantages from tobacco on health which are reported in the medical literature. But the risk of caries among these tobacco users, such as chewers and smokers, is still debatable. Hence, the present study aims to determine the prevalence of dental caries among tobacco chewers and smokers. Materials and methods: In this study, 389 individuals were included. Out of 389 individuals, 304 were men and 85 were women aged between 18 and 60 years. They were classified into two groups. Group A had 207 individuals with habitual tobacco chewing, and Group B had 182 individuals with habitual tobacco smoking and provided a 6 months history. The DMFT index (Decayed, Missing, and filled teeth index-WHO modification 1997) was used to assess caries. Results: The study revealed a higher prevalence of dental caries among tobacco chewers compared to tobacco smokers. The DMFT scores were higher among gutka chewers compared to other types of tobacco use. The lower posterior tooth region showed higher dental caries in tobacco chewers compared to smokers. Conclusion: The higher presence of caries in the tobacco chewing group is due to the presence of sweeteners, which act as cariogenic agents. Similarly, smokers have a thiocyanate component that acts as an anticariogenic agent; therefore, the prevalence of caries was lower in tobacco smokers.